PENGARUH PENGGUNAAN MODEL PERIODISASI GELOMBANG (UNDULATING) DALAM KEKUATAN TERHADAP PENINGKATAN POWER ENDURANCE - Mamay Maemunah, - (2020)
Power endurance is needed to support the performance of one of the models used, namely the undulating model. The problem that occurs is when endurance is needed and what kind of program is good to use according to the needs of athletes in the sport itself. The purpose of this study was to see how to increase the endurance of the upper body (arm) and lowerboy (leg) after using the undulating periodization model. The research method used was a bad experiment The One-Group Pretest-Posttest Design. The sample used was the second level students of Sport Science FPOK UPI which connected 15 people. Instrument for measuring upper body endurance, clapping push ups, while measuring the lower body with jumping hurdles. The data analysis used was the Paired Simple T Test. The results showed that the Periodization Model had a significant impact on increasing upper and lower body resistance.